A case of remitting hemicrania continua with seasonal variation and clustering: a diagnostic confusion with cluster headache. Issue 5 (19th May 2019) - Prakash, Sanjay; Rawat, Kalu Singh
Abstract : Hemicrania continua (HC) is an indomethacin responsive primary headache that is characterised by a continuous strictly unilateral headache with periodic exacerbations. About 15% may have a remitting subtype of HC. Herein, we are reporting a 36-year-old man who had a 5-year history of episodic right-sided headaches. The headaches used to occur in a discrete series lasting 4–6 weeks, separated by pain-free remissions of 10–11 months. In each relapse, he had continuous background pain with superimposed exacerbations. The superimposed exacerbations were 1–2 attacks per day, lasting for 2–5 hours, and were associated with ipsilateral cranial autonomic symptoms. However, the patient did not respond to usual therapies of custer headache (CH). He had a complete response to indomethacin. We suggest that remitting subtype of HC may mimic CH. A therapeutic trial of indomethacin should be done in all strictly unilateral headaches who are not responding to other drugs.